2011
DOI: 10.1128/jvi.01787-10
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Helper-Dependent Adenovirus DNA into Chromatin Promotes Efficient Gene Expression

Abstract: Helper-dependent adenovirus (hdAd) vectors have shown tremendous potential in animal models of human disease in numerous preclinical studies. Expression of a therapeutic transgene can be maintained for several years after a single administration of the hdAd vector. However, despite the long-term persistence of hdAd DNA in the transduced cell, little is known of the fate and structure of hdAd DNA within the host nucleus. In this study, we have characterized the assembly of hdAd DNA into chromatin in tissue cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 78 publications
3
71
0
Order By: Relevance
“…3A, the exclusive binding of H3.3 on viral chromatin was observed at all the regions that we tested, with a gradual increase as infection proceeded. This finding is consistent with data from a recent report of a helper-dependent Ad vector (HdAd) indicating that histone H3.3 is specifically deposited onto HdAd DNA by HIRA, an H3.3-specific histone chaperone (34). Since HdAd alone does not undergo its DNA replication, the chromatin state of HdAd may reflect that of wild-type Ad in early phases of infection (13,34).…”
Section: Cells and Virusessupporting
confidence: 91%
“…3A, the exclusive binding of H3.3 on viral chromatin was observed at all the regions that we tested, with a gradual increase as infection proceeded. This finding is consistent with data from a recent report of a helper-dependent Ad vector (HdAd) indicating that histone H3.3 is specifically deposited onto HdAd DNA by HIRA, an H3.3-specific histone chaperone (34). Since HdAd alone does not undergo its DNA replication, the chromatin state of HdAd may reflect that of wild-type Ad in early phases of infection (13,34).…”
Section: Cells and Virusessupporting
confidence: 91%
“…Like the herpes simplex virus 1 genome, the HAdV genome was shown to associate with H3.3 (50,51), suggesting that HAdV DNA is chromatinized. The core/DNA complex enters the nucleus and is decondensed prior to the onset of early viral gene transcription (52).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, genome-wide analysis has revealed acetylated histones across the hAd genome (15). These include H3, H3.1, and H3.3, which are acetylated at K9 and K14, presumably by GCN5, and also at K18, which is presumably acetylated by p300/CBP (15,22,41), yet no direct role for E1A or GCN5 in this process was demonstrated in either report. Consistent with previous reports, we show here that E1A is not required for H3 deposition and K9/K14 acetylation, as cells infected with hAd with deletion of E1A (⌬E1A) still acquire both H3 and K9/K14-acetylated H3 (H3-Ac) on the viral E4 promoter (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GCN5 has a well-established role as a transcriptional coactivator that acetylates histone H3 at K9 and K14 and facilitates transcriptional elongation in the context of the SAGA complex (4,9,32,40). Although the viral genome is initially devoid of cellular histones, recent reports demonstrate that histones, including H3, bind to viral DNA during the early phases of infection (15,22,41). These reports indicated that the H3 associated with the viral genome is acetylated at K9 and K14 during virus infection, likely by GCN5.…”
Section: Figmentioning
confidence: 98%
See 1 more Smart Citation